National and Transnational Dimensions of Memory in Matar a todos and Paisito. - Rocha, Carolina (Hispanic Research Journal, 2016)
This article investigates the national and transnational dimensions of the representation of memory in two contemporary Uruguayan films, Esteban Schroeder’sMatar a todos(Kill Them All, 2007) and Ana Diez’sPaisito(Small Country, 2008). These films revisit the traumas and after-effects of the Southern Cone dictatorships that came to power in the early and mid-1970s. As co-productions,Matar a todosandPaisitorely on the representation of prosthetic memories, but the artificial nature of these memories may be problematic for different audiences. Thus, this article not only considers these films’ depiction of a traumatic past, but also their circulation in and beyond Uruguay and the challenge of engaging transnational audiences.